National Education Policy 2020: The Key To Development In India (Volume-2) - Mishra, Pratima; Deepak (AG Volumes, 2025)
"National Education Policy 2020: The Key to Development in India" provides an in-depth exploration of the NEP 2020, which promises to revolutionize the Indian education system. This book comprehensively analyzes the key components of the policy, from curriculum reforms to the emphasis on multilingual education, and the introduction of new pedagogical methods. It sheds light on how the policy addresses critical issues such as access, quality, and equity, ensuring that education becomes more inclusive and equitable for all segments of society. By focusing on areas such as early childhood education, vocational training, teacher empowerment, and the integration of technology, this book illustrates how NEP 2020 aims to create a holistic and well-rounded educational experience. It highlights how these changes will contribute to India’s socio-economic development by nurturing a skilled and knowledgeable workforce, capable of meeting global challenges. This book is not only a guide to understanding the intricacies of the National Education Policy but also a call to action for educators, administrators, and citizens to actively participate in shaping a better future for India through education. It is a timely and crucial resource for anyone seeking to understand the pivotal role education will play in India’s growth and development in the years to come.